New records of Endectyon (Endectyon) xerampelina (Lamarck, 1814 (Demospongiae: Axinellida: Raspailiidae) from the Tropical Western Atlantic Ocean, with comments on its distribution and type locality - Sandes, Joana; Recinos, Radharanne; Pinheiro, Ulisses; Muricy, Guilherme (Zootaxa, 2019)
The demosponge genus Endectyon is characterized by the presence of acanthostyles with recurved or clavulate spines. Two subgenera are recognized, Endectyon and Hemectyon, distinguished mainly by the acanthostyles being located only in the periphery of the axial skeleton in Endectyon, or forming the ectosomal brushes in Hemectyon. Sixteen species are known worldwide, of which only two were reported from the Western Atlantic Ocean. However, the type locality of Endectyon xerampelina is uncertain, and it could be located either in the Western Atlantic or in Australia. In the present study, we describe new records of E. xerampelina from the Brazilian coast and propose that Raspailia (R.) johnhooperi from the Guyana shelf is a junior synonym of E. xerampelina. Our results support the hypothesis that the type locality of E. xerampelina is located somewhere in the Tropical Western Atlantic Ocean and also that the species belongs to the subgenus Endectyon (Endectyon). We amended the diagnosis of the subgenus Endectyon (Endectyon) to account for the variability of acanthostyle shape in E. (E.) xerampelina, assigning greater taxonomic value to the position of the echinating megascleres than to their shape and pattern of spination.